2009
DOI: 10.1016/j.engappai.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based distributed manufacturing control: A state-of-the-art survey

Abstract: a b s t r a c tManufacturing has faced significant changes during the last years, namely the move from a local economy towards a global and competitive economy, with markets demanding for highly customized products of high quality at lower costs, and with short life cycles. In this environment, manufacturing enterprises, to remain competitive, must respond closely to customer demands by improving their flexibility and agility, while maintaining their productivity and quality. Dynamic response to emergence is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
349
0
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 701 publications
(392 citation statements)
references
References 63 publications
1
349
0
21
Order By: Relevance
“…Agents are units of a software system typically characterized by autonomy, intelligence, adaptation, co-operation [37] and reactivity [38]. The reactivity is the feature that makes an agent ready for receiving external messages and responding to them in a sufficiently short time.…”
Section: Multi-agent Systemmentioning
confidence: 99%
“…Agents are units of a software system typically characterized by autonomy, intelligence, adaptation, co-operation [37] and reactivity [38]. The reactivity is the feature that makes an agent ready for receiving external messages and responding to them in a sufficiently short time.…”
Section: Multi-agent Systemmentioning
confidence: 99%
“…In the process execution, the PA agent interacts with the RA and QCA agents that are able to execute the k individual operations belonging to the process plan. At the end of one operation execution, the next operation to be executed is selected by the function represented by the timed transition t 5 , followed by the execution of the "supervises the operation execution" function represented by the timed transition t 6 . This transition can be expanded into a refined Petri nets model containing the details about the functions to supervise the execution of the operation.…”
Section: Fig 2 Behaviour Model For the Product Agentmentioning
confidence: 99%
“…In fact, the distributed nature of the multi-agent systems approaches suggests the definition of distributed control functionalities based on autonomous agents that account for the realization of efficient, flexible and robust overall plant control, exhibiting modularity adaptation and re-configurability. Several applications of multi-agent systems at factory level were reported in the literature (e.g., see [6] and [7] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the promising perspective of using MAS solutions to address the challenge of achieving adaptive production systems, only few industrial applications were reported in the literature, e.g. the application in a factory plant of Daimler Chrysler [4] and some experiences from Rockwell Automation [5] and Schneider Electric [6] (see [7] and [8] for a deeply analysis). Several reasons were the rear tub) and the operation parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%